Teaching feints to handball beginners : Preliminary results - Henigman, David; Katarina Ohnjec (Annales Kinesiologiae, 2022)
The aim of this preliminary research was the evaluation of a two-month program for improvement of single forward feint to the left with passage to the right, and single forward feint to the right with passage to the left by „shifting opponents” hand. Sixteen young male handball players, aged 9.64 ± 0.87 years, participated in this study. The program was being implemented in two months, in which 18 training sessions (35%) were conducted for the improvement of feint skills, from 52 training sessions overall. Initial video recording was accomplished at the beginning of the period, and final video recording at the end. Videos were analyzed by three experts, using grading list and detailed grading criteria. The basic parameters of descriptive statistics were determined for both variables. The metric characteristics of the expert estimation contribution were analysed through measures of reliability (Cronbach's α) and homogeneity (average item intercorrelation). The non - parametric (Wilcoxon t-test) method was used to analyse changes in the levels of feint performance at different time points. The results indicate satisfactory reliability and homogeneity of the tests (α1=0.90; r1=0.80; α2 =0.86; r2=0.87). By insight into results, the significant difference is spotted between the initial and final state of both motor skills acquisition (T1 = 114.5, p= 0.01; T2 =7.00; p= 0.01). The limiting factors can be seen in the sample size of this entity, the absence of the control group as well as the validated evaluation of the instrument.